COVID-19 Knowledge amongst Dentists and Evaluation of the Dental Infection Prevention Protocol - AlZoubi, Hamed; Abu-Helalah, Munir; Alshraideh, Hussam; Alkhasawneh, Mahmoud (Jordan Medical Journal, 2021)
Background and Objectives: Dentists are at higher risk of acquiring corona virus disease -19 (COVID-19). + The objective of the study is to assess the level of knowledge regarding COVID-19 among dentists and to evaluate the implementation of the infection prevention protocol. Materials and Methods: An online questionnaire was administered to 188 Jordanian dentists. The questionnaire was composed of three sections: demographic and professional data, knowledge of COVID-19 and the implemented infection prevention protocol. Results: The overall knowledge of COVID -19 common symptoms was high (<90%) among all participants. However, knowledge of specialists or who received infection prevention education regarding uncommon symptoms was significantly higher than others (p-value ≤ 0.05). About one-third of all participants correctly identified the scientific name of the causative virus (SARS-CoV-2) with no significant statistical difference. Most participants agreed that the infection prevention protocol is easy to read but the items are scarce. Female dentists were more likely to advise others to use the protocol (p-value = 0.01), and dentists with postgraduate education in infection prevention within the last three years answered that they will follow the protocol strictly (p-value = 0.03). Specialists and those who received postgraduate infection prevention education showed more knowledge regarding the specific measures for infection prevention. Conclusion: The overall knowledge of COVID-19 was high among dentists. Infection control protocol for dentists was easy to read and comprehensive but the items required to implement it such as personal protective equipment are scarce. This is expected considering the worldwide high demand on such items.